Reductive Leaching Of Low Grade Manganese Ore Using Bamboo Saw Dust - Ismail, Suhaina (2014)
Extraction of manganese (Mn) from low grade manganese ore (LGMO) through reductive leaching was studied in this research work. The reductive leaching process was done in acidic medium (H2SO4) and bamboo sawdust (BSD) was used as reducing agent. Mineral phase characterization on LGMO showed that the ore consist of phases of pyrolusite, α-quartz and goethite. Meanwhile, the biomass composition of BSD used in this work contains 38.96% cellulose, 26.95% hemicellulose and 25.86% lignin. In determination of optimum Mn recovery, design of experiment through a sequenced response surface method (RSM) was done. It was observed that the most significant variable on the leaching of LGMO is temperature, followed by concentration of H2SO4 and mass of BSD. Extraction of Mn above 95% with low dissolutions of Fe (<30%) and Al (<10%) was achieved at leaching temperature between the range of 90oC≤T≤110 oC; H2SO4 concentration of 1.5M≤H2SO4≤ 2.5M and BSD mass of 7.5g. The reaction kinetics of this leaching process was determined, and it was observed to fit the model of 1